Effect of creep ageing on the corrosion behaviour of an Al–Cu–Li alloy. (1st July 2022) - Jiang, Bo; Wang, Chao; Song, Renguo; Li, Shichen; Cao, Fuhua; Yi, Danqing
Abstract: Creep ageing of Al–Cu–Li alloys induces precipitation of T1 (Al2 CuLi) and a high fraction of low-angle grain boundaries (LAGBs) and dislocations in grain interior, factors potentially contributing to corrosion. Qualitative/quantitative analysis of precipitates and quasi-in-situ EBSD observations of stress free and stress added alloy reveal that fine dense precipitation of T1 in grain interior and suppressed precipitation along grain/subgrain-boundary induced by stress adding make the corrosion mode evolve from intergranular to intragranular, and grain orientation displays as the most relevant metallurgical parameter for the localised corrosion although the fraction of LAGBs and dislocations have been greatly improved by stress loading. Highlights: Al-Cu-Li alloys are formed by creep deformation during ageing. Precipitation of T1 is an important factor for localised corrosion in these alloys. The formation of T1, LAGBs and dislocations are improved by stress adding. Corrosion depends chiefly on the orientation of the grains. As stress increases, corrosion changes from inter- to intra-granular.